(untitled) (Nepalese Journal of Management Research, 2024)
This study aims to evaluate the customer dimension of the balanced scorecard approach in the banking industry of Nepal and to compare the state of the balanced scorecard from the customer dimension in state-owned banks, private banks, and joint-venture banks. It employs a descriptive method of study. A questionnaire survey is used to collect data for this study. The results show that the top five elements of the customer dimension of the balancing scorecard technique are believed to be customer retention, brand image, minimum customer complaints, careful staff to provide service and customer acquisition. The important factors that follow them include sufficient staff to provide services to customers, best appearance and friendliness of staff, customer profitability, distinctive product/service attributes, increasing market share, offering social/community services, in-time customer services, satisfied customers, and skillful and competent staff. However, market penetration success is thought to be the least important factor in the customer dimension of the balanced scorecard. Therefore, to be successful, today’s financial institutions must gather information from customers, use it to create a plan that will fulfill their demands, and then put that strategy into action by being receptive to their needs and desires.